Factors Influencing Customer Satisfaction with Halal Cosmetics: An Online Purchasing Study of Generation Z Muslim Women - Bayu Arie Fianto; Bena Mutiara Dwi Ulfa; Zhahirah Adriana Rahmadany (Shirkah: Journal of Economics and Business, 2025)
Customer loyalty in the beauty product sector, particularly for halal cosmetics, has been underexplored despite its importance in marketing research. This study explores the determinants of customer satisfaction and loyalty towards halal cosmetics in Indonesia. Data were collected from 215 Generation Z Muslim women who have made multiple purchases from the official online store of a halal cosmetic brand through an online questionnaire. The data were further analysed by employing Structural Equation Modelling-Partial Least Square (SEM-PLS). The results showed that overall quality and perceived value significantly influence customer satisfaction, which in turn affects loyalty. However, perceived risk did not significantly impact satisfaction. It was further revealed that customer satisfaction has a significant influence on the customer loyalty to halal cosmetics. These findings highlight the need for brands to consistently deliver high-quality products and enhance perceived value to foster lasting customer relationships. Given Generation Z's potential as customers but known brand-switching tendencies, this study offers insights into their loyalty and satisfaction when purchasing halal cosmetics online. Strategic emphasis on satisfaction-building efforts can ultimately strengthen brand loyalty among Generation Z consumers in the competitive halal cosmetics market. Hence, understanding the factors that drive customer satisfaction and loyalty in online purchases is essential for halal cosmetic companies to develop effective retail strategies.